2017
DOI: 10.5812/semj.59461
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Self-Reported Sleep Problems and Some Factors Affecting It Among the Elderly in Amirkola

Abstract: Background: Knowing the quality of sleep in the elderly and its effective factors helps to take measures in increasing or decreasing their effect. Objectives: The aim of this study is to determine the sleep problems and its effective factors in the elderly of Amirkola, the northern part of Iran. Methods: This cross-sectional study was extracted from the Amirkola health and ageing project (AHAP), which is a cohort project regarding the elderly in the city of Amirkola, the northern part of Iran. Since 2011, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(37 reference statements)
0
7
1
Order By: Relevance
“…Our study showed that 71.1% of respondents had insomnia which is in line with other studies in India (Ahmad et al, ), Egypt (El‐Gilany, Saleh, Mohamed, & Elsayed, ), Korea (Jeon & Choi‐Kwon, ) and Nepal (Shrestha et al, ). On contrary, some other studies in the USA (George et al, ; Mendoza‐Meléndez et al, ; Miner et al, ), Singapore (Sagayadevan et al, ), Iran (Hosseini et al, ), South Korea (Kim et al, ) and China (Luo et al, ; Tsou, ) have shown lower prevalence than the current study. These variations in insomnia prevalence may be attributed to the absence of standardization in the definition of insomnia.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our study showed that 71.1% of respondents had insomnia which is in line with other studies in India (Ahmad et al, ), Egypt (El‐Gilany, Saleh, Mohamed, & Elsayed, ), Korea (Jeon & Choi‐Kwon, ) and Nepal (Shrestha et al, ). On contrary, some other studies in the USA (George et al, ; Mendoza‐Meléndez et al, ; Miner et al, ), Singapore (Sagayadevan et al, ), Iran (Hosseini et al, ), South Korea (Kim et al, ) and China (Luo et al, ; Tsou, ) have shown lower prevalence than the current study. These variations in insomnia prevalence may be attributed to the absence of standardization in the definition of insomnia.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous studies have identified various factors associated with insomnia among the older population. For instance, gender, educational level, occupational status, financial dependency, marital status, accompanying chronic diseases, medical comorbidities, drug use, current smoking, caffeine intake before bedtime and environmental factors were identified as associated factors in one or more studies (George et al, ; Hosseini, Saadat, Esmaili, & Bijani, ; Luo et al, ; Mendoza‐Meléndez, Jimenez‐Correa, Gallegos‐Cari, Ayala‐Guerrero, & Jiménez‐Anguiano, ; Miner et al, ; Sagayadevan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gender, drug use, marital status, chronic pain, depression, urinary incontinence, education level, metabolic syndrome, occupation, MMSE, hypnotics, and diabetes were associated with the prevalence of sleep disorders. According to the logistic regression analyses, 12-month back pain (OR = 1.64, P = 0.003), hypnotic drugs (OR = 1.5, P = 0.03), depression (OR = 1.66, P = 0.001), age range of 75 to 79 years old (OR = 0.58, P = 0.01), accompanying chronic disease (OR = 1.15, P < 0.001), and MMSE (OR = 1.59, P = 0.003) had a signicant role in sleep 22 problems. 21.…”
Section: Materials Methodsmentioning
confidence: 96%
“…Problems with sleep have also been associated with an increased risk of hospitalization and increased mortality. 3 Therefore, the present study was envisaged to assess the sleep quality among the elderly and the factors associated with it.…”
Section: Introductionmentioning
confidence: 99%